2021
DOI: 10.3389/fonc.2021.646779
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics Identified Lyso-Phosphatidylcholine and Phosphatidylethanolamine as Potential Biomarkers for Diagnosis of Laryngeal Cancer

Abstract: BackgroundLaryngeal cancer (LaC) remains one of the most common tumors of the respiratory tract with higher incidence in men than in women. The larynx is a small but vital organ on the neck. The dysfunction of the larynx can cause serious health problems such as hoarseness, respiratory distress, and dysphonia. Many lipids (e.g. phospholipid, cholesterol, fatty acid) have been recognized as a crucial role in tumorigenesis. However, the lipid biomarkers are lacking and the lipid molecular pathogenesis of LaC is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Moreover, the levels of Lysophosphatidylcholines (LPC) 16:0 decreased in the tumor in comparison to the adjacent healthy tissue. This result is consistent with previous relevant findings in which LPC 16:0 significantly decreased in laryngeal cancer serum samples and prostate cancer tissues, highlighting the early diagnostic potential of this lipid biomarker [33,35]. This point can be supported by the mutual conversion of PCs and LPCs.…”
Section: Lipidome Differences Between Tumor and Non-tumor Areas Of Pa...supporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the levels of Lysophosphatidylcholines (LPC) 16:0 decreased in the tumor in comparison to the adjacent healthy tissue. This result is consistent with previous relevant findings in which LPC 16:0 significantly decreased in laryngeal cancer serum samples and prostate cancer tissues, highlighting the early diagnostic potential of this lipid biomarker [33,35]. This point can be supported by the mutual conversion of PCs and LPCs.…”
Section: Lipidome Differences Between Tumor and Non-tumor Areas Of Pa...supporting
confidence: 93%
“…These findings are in good agreement with previous studies that have proposed the spatial confinement of PCs to specific cancer models [29][30][31]. It is well known that PCs are the most predominant components of phospholipids for biological membranes; PC metabolism is altered in the onset and development of many tumors [32,33]. In particular, the elevated levels of PC 32:1 and PC 34:1 have been positively correlated to the cancerous areas of colorectal, prostate, and breast cancer tissues [29][30][31].…”
Section: Lipidome Differences Between Tumor and Non-tumor Areas Of Pa...supporting
confidence: 91%
See 1 more Smart Citation
“…Our results further strengthen the association between blood LPC levels and acute inflammation. Moreover, LPCs have been reported as candidate biomarkers for cancer and diabetes, with which chronic inflammation is associated 25,31,32 . However, we found that plasma LPC(14:0) concentrations were higher in patients with the chronic inflammatory lung diseases IIP, CTD, COPD, and BrAs, than that in patients with DILD.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated genes included Gpx7, Gpx3, Cyp2e1, Ptges, Ptgis while Ptgds, Plb1, Cyp2b19, Ggt1, Pla2g2e, Pla2g2d, Alox12 were dramatically downregulated (Figures 6A, 7A, 8A). Arachidonic acid is one of the major polyunsaturated fatty acids in mammals (Yu and Wang, 2021). In consideration of the significant decrease of AA-residue-enriched LPCs (e.g., LysoPC…”
Section: Crs Significantly Alters Genes Expression Related To Metabol...mentioning
confidence: 99%